Long-term Clinical Follow-up in 265 Patients with Deep Venous Thrombosis Initially Treated with either Unfractionated Heparin or Dalteparin: A Retrospective Analysis - Holmström, M.; Åberg, W.; Lockner, D.; Paul, C. (Thrombosis and Haemostasis, 1999)
The primary objective of this retrospective study was to describe the frequency of a post-thrombotic syndrome in 265 patients previously treated for deep venous thrombosis (DVT). The secondary objectives were to document the frequency of recurrent venous thromboembolism (VTE) and mortality, especially from malignant disease. The patients were evaluated 5-14 years after inclusion in three randomized trials comparing continuous intravenous (i. v.) infusion of unfractionated heparin (UFH) (n = 85) with a low molecular weight heparin (LMWH), dalteparin (n = 180). The median post-thrombotic score at follow-up was 2 (range 0-8). In a multiple step-wise regression analysis the post-thrombotic score was significantly higher among patients with initial proximal DVT (p = 0,0001) as compared with those who had distal DVT. A recurrent venous thromboembolic event was diagnosed in 29,4% of the patients treated with dalteparin and in 23,5% of the patients treated with UFH (ns). A secondary risk factor for venous thromboembolism and a longer duration of treatment with oral anticoagulants (OAC) were significantly associated with a lower risk for recurrent VTE, whereas malignant disease diagnosed during follow-up was associated with a higher risk. During follow-up a total of 40,7% of patients had died. No difference in total mortality or mortality from malignant disease was demonstrated between the two drugs. In conclusion, a severe post-thrombotic syndrome occured relatively infrequent. considering the long observation period. Proximal DVT was significantly associated with a more severe post-thrombotic syndrome. After 14 years follow-up, no significant differences were observed in overall mortality, mortality from malignant disease or recurrent VTE between UFH- and dalteparin-treated patients. Malignant disease was a risk factor for recurrent VTE, the presence of a secondary risk factor and a longer duration of treatment with OAC decreased the risk for recurrent VTE.